Determining feeding events and prey encounter rates in a southern elephant seal: a method using swim speed and stomach temperature - JM Horsburgh; M Morrice; MA Lea; MA Hindell (2008)
Determining feeding events and prey encounter rates in a southern elephant seal: a method using swim speed and stomach temperature